COVID vaccine evaluation of barriers and resources among families of children with diagnosed allergies - Gooding, Gregory D.; Protudjer, Jennifer L.; Gabrielli, Sofianne; Mulé, Pasquale; Shand, Greg; Zhang, Xun; McCusker, Christine; Noya, Francisco J.; Harvey, Maria; Chalifour, Mélodie; Sicard, Catherine; Abrams, Elissa; et al. (Frontiers in Allergy, 2023)
Background: We aimed to determine vaccine hesitancy and the main barriers associated with the SARS-CoV-2 (COVID-19) vaccination among families of children diagnosed with food/drug/ environmental allergies. Methods: Between May and June 2021, we approached 146 families seen at the outpatient allergy clinic at the Montreal Children’s Hospital and a community allergy practice were invited to complete an anonymous online survey on COVID-19 and vaccination attitudes and behaviour. Uni and multivariate logistic regressions were compared to estimate factors associated with vaccine Results Among all patients, 24.1 % reported vaccine hesitancy. The large majority of parents (95.2%) believed that vaccines work. The most common barrier to vaccination was fear of adverse side effects (57%). One-third of participants (31.5%) reported that a history of food, venom and drug allergy was a contraindication for COVID-19 vaccination. Fifty-nine (60.8%) participants stated that dissemination of additional information would increase their willingness to be vaccinated. Most (96.9%) parents reported that their children’s vaccinations were up to date. Hesitant families were more likely to be parents of children aged 6 - 10 years, be of Asian descent, report that mRNA vaccines are riskier than traditional vaccines, and report that the vaccine should not be given if the child has a history of allergic reaction to vaccines. Conclusion: Vaccine hesitancy exists mainly among certain ethnic groups and families with young children. Allergies to food, venom and drug allergy are commonly perceived as contraindications for COVID-19 vaccination. Knowledge translation activities addressing parental concerns will help increase vaccination rates.